2008
DOI: 10.1158/1940-6207.capr-08-0042
|View full text |Cite
|
Sign up to set email alerts
|

Difluoromethylornithine Plus Sulindac for the Prevention of Sporadic Colorectal Adenomas: A Randomized Placebo-Controlled, Double-Blind Trial

Abstract: Preclinical studies of chemoprevention drugs given in combination at low doses show remarkable efficacy in preventing adenomas with little additional toxicities, suggesting a strategy to improve risk to benefit ratios for preventing recurrent adenomas. Three hundred seventy-five patients with history of resected (≥3 mm) adenomas were randomly assigned to receive oral difluoromethylornithine (DFMO) 500 mg and sulindac 150 mg once daily or matched placebos for 36 months, stratified by use of low-dose aspirin (81… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
447
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 459 publications
(458 citation statements)
references
References 32 publications
10
447
0
1
Order By: Relevance
“…A recent randomized trial showed that the combination of DFMO and the nonsteroidal anti-inflammatory drug (NSAID) sulindac was associated with a 70% reduction in the recurrence of sporadic colorectal adenomas (13). This study lends further support for the evaluation of DFMO as an inhibitor of epithelial carcinogenesis.…”
Section: Introductionmentioning
confidence: 61%
“…A recent randomized trial showed that the combination of DFMO and the nonsteroidal anti-inflammatory drug (NSAID) sulindac was associated with a 70% reduction in the recurrence of sporadic colorectal adenomas (13). This study lends further support for the evaluation of DFMO as an inhibitor of epithelial carcinogenesis.…”
Section: Introductionmentioning
confidence: 61%
“…Unfortunately, the use of celecoxib has been associated with an increased risk of adverse cardiovascular effects (24). Notably, low doses of the antiinflammatory sulindac and an investigational compound difluoromethylornithine (DFMO) prevented colon polyp recurrence by 70% and the recurrence of advanced adenomas by 92% in a recent phase III trial (25). These results clearly demonstrate the idea of combination prevention or therapy or convergent prevention and therapy, which will be discussed later in this perspective.…”
Section: Cancer Prevention In the United Statesmentioning
confidence: 86%
“…The Food and Drug Administration still forbids the use of two experimental drugs in clinical prevention trials, in spite of the fact that there is overwhelming evidence that combinations can be much safer and more effective than single agents 7 . Further appreciation and understanding of the concept of 'risk' is also essential.…”
Section: The Big C -For Chemopreventionmentioning
confidence: 99%